Analisis SWOT sebagai Strategi Pengembangan Usaha pada UMKM Jasa Digital Printing (Studi Kasus Diza Digital Printing di Kecamatan Banjaran) - Dini Indria Zahira; Hendar Rubedo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The development of the creative industry and digital printing services requires micro, small, and medium enterprises (MSMEs) to implement appropriate business development strategies in order to remain competitive and sustainable. Diza Digital Printing, a digital printing MSME located in Banjaran District, still faces several challenges, including limited production capacity, poorly organized administrative systems, suboptimal promotional activities, and the absence of business legality. This study aims to analyze the internal and external conditions of the business and to formulate appropriate development strategies using the SWOT Analysis approach. This research employs a qualitative descriptive method, with data collected through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model and further formulated into the SWOT Matrix, IFAS, EFAS, and QSPM. The results show that Diza Digital Printing is positioned in Quadrant I (Strength–Opportunity), indicating that the business has strong internal capabilities to take advantage of market opportunities. The priority strategies recommended include restructuring the administrative system, completing business legality, strengthening digital promotion, and gradually increasing production capacity.